OPF paper: wet strength in paper making from oil - Shahudin, Fakharudin; Zakaria, Haslizaidi; Jaballudin, Norazura (Universiti Teknologi MARA, Kedah, 2023)
This study is about the oil palm fronds (OPF) as raw materials and its contents to make pulp and paper. The paper is consisted a network of cellulose fibre bonded together. Different way treated paper different achievement of strength. Each of the fibre contact is very sensitive to water and easily to break as the water wet the fibres which swell. This study was conducted in view of exploring and the paper making potential be as filter paper function with addition of wet strength resin to improve the quality of Oil Palm Fronds (OPF) paper. Bleaching process is done in early stages to remove residual lignin and make it more brighter than OPF raw colour. The addition of Melamine Urea Formaldehyde (MUF) into the Oil Palm Frond pulp fibre to improve the quality and increase the wet tensile strength in paper. Melamine Urea Formaldehyde (MUF) gives higher degree of interatomic attraction which is hydrogen bonding than normally occurs in paper. The values of wet tensile strength between both were compared which are 17.23 g/nm2 for Oil Palm Fronds (OPF) Paper with Melamine Urea Formaldehyde (MUF) and 26.44 g/nm2 for commercial filter paper. Oil Palm Fronds (OPF) as raw material with addition of glue showed tremendous potential can be like commercial filter paper as the result between both showed slightly similar in mechanical and chemical testing.